Penggunaan Kartu Aksara Jawa Nglegeno Berbasis Edugame dalam Pembelajaran Bahasa Jawa di Madrasah Ibtidaiyah - TARSIM, TARSIM (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
This study aims to make learning more fun and make it easier to memorize the Javanese script nglegeno in Javanese subjects in Madrasah Ibtidaiyah through card games Javanese characters and their sounds. For data retrieval obtained through observation, interviews, tests, and documents. The technique used to analyze data there are three components, namely data reduction, data presentation, and conclusion making. The results of this study are the use of Javanese letters cards and edugame-based Javanese sound cards are expected that active MI / SD educator participants in reading Javanese script Nglegena will increase and be able to read them well.